(untitled) (Salam International Academic Journal, 2024)
The Shanghai Cooperation Organization (SCO) was originally established to address territorial and border disputes among its member states—issues that emerged in the aftermath of the Soviet Union’s dissolution and the subsequent independence of several Central Asian republics. Initially operating under the framework of the “Shanghai Five,” the organization, spearheaded by China and Russia, expanded with Uzbekistan’s inclusion, evolving into the “Shanghai Six.” On June 15, 2001, it was officially reconstituted as the Shanghai Cooperation Organization (SCO), broadening its objectives to encompass economic cooperation and fostering regional development among newly sovereign states. Given the founding roles of China and Russia within the SCO, contemporary geopolitical developments—including Russia’s military intervention in Ukraine, escalating tensions surrounding Taiwan, and the United States’ and NATO’s strategic opposition—have significantly intensified global political and military rivalries. These developments are propelling the international system toward a more pronounced multipolar order. On one side, China’s rapid economic ascent and Russia’s assertive foreign policy under President Vladimir Putin, and on the other, NATO’s eastward expansion alongside U.S. strategic maneuvers aimed at constraining China’s rise and exerting pressure on Russia, have contributed to growing instability characterized by military buildup and competitive strategic positioning. Within this context, a central question arises: Can the SCO, particularly with the participation of key actors such as Russia, China, and Iran—three states often positioned as adversaries to U.S. influence—serve as an emergent security alliance akin to an "Eastern NATO"? This study hypothesizes that geopolitical shifts in Eastern Europe, the Far East, and Central Asia provide conductive conditions for the SCO’s transformation into a collective defense mechanism capable of counterbalancing NATO’s influence. By consolidating the strategic power of its member states, Russia and China—alongside others—may effectively challenge expansionist Western policies, particularly in the Eastern hemisphere. This recalibration of global power dynamics could facilitate the transition from a predominantly U.S.-led unipolar structure toward a more stable multipolar order